Acute rheumatic fever and multiple drug hypersensitivity: a case report - Fahira, Cindy; Suryana, Ketut (International Journal of Advances in Medicine, 2026)
Acute rheumatic fever (ARF) is an autoimmune-mediated inflammatory disorder precipitated by infection with group A Streptococcus (GAS) infection. The underlying pathogenesis is attributed to molecular mimicry, wherein antibodies directed against GAS antigens cross-react with host tissues. Diagnosis is established based on clinical evaluation using the revised Jones criteria in conjunction with laboratory evidence of recent GAS infection. Management involves antibiotic therapy, anti-inflammatory agents, and long-term prophylactic strategies to prevent recurrence. One of the potential adverse effects associated with these pharmacologic agents is drug hypersensitivity reactions (DHR). The recommended diagnostic approach to DHR is a graded challenge by introducing drugs safely and optimally under a threshold dose until the usual daily dose is reached. In the present case, due to the patient’s documented history of multiple drug hypersensitivities, a graded drug challenge was performed to ensure medication tolerance and minimize the risk of hypersensitivity.